Identification of Gayo arabic coffee beans and powder using the FTIR-PCA combination method. Issue 1 (February 2021) - Akbar, Z; Idroes, R; Ginting, B; Karma, T; Rahimah, S; Helwani, Z; Yusuf, M
Abstract: The identification of Gayo Arabica coffee beans and coffee powder has been done to classify coffee plantation from several different regions using FTIR Spectroscopy and Principal Component Analysis (PCA). Samples were taken by purposive sampling from the Arabica coffee plantations in Pegasing, Jagong, and Celala areas, Aceh Tengah Regency, and also in Bandar, Permata, and Wih Pesam areas, Bener Meriah Regency. FTIR analyzed both the dry Gayo Arabica coffee beans and powder in the wavelength range of 4000 cm −1 -400 cm −1 . The spectra resulted were analyzed using PCA. FTIR spectra show the absorption of typical functional groups of caffeine, namely O-H (3400 cm −1 ), C-H aromatic (2900 cm −1 ), C-H aliphatic (2800 cm −1 ), C=O (1743 cm −1 ), C=C ( 1640 cm −1 ), C=C aromatic (1550 cm −1 ), C-H alkanes (1450 cm −1 ) and C-N (1240 cm −1 ). There was a loss of absorption of C=O and C-N groups in coffee powder samples from the Pegasing, Jagong, and Permata areas caused by high-temperature heating during the coffee powder making process. The PCA showed that coffee bean samples could be distinguished properly based on the coffee origin location, namely Aceh Tengah and Bener Meriah Regencies. Meanwhile, coffee powder samples showed poor separation of PCA plot patterns between coffee powder from the two regions. It can be concluded that the PCA method can be used for the classification of both Gayo Arabica coffee beans and powder, where the classification of beans is better than powder.